Decentralization and Regional Autonomy in Indonesia: Implementation and Challenges (ISEAS, 2009)
With contributions from prominent authors who have looked at the process closely, this overview of the first few years after decentralisation covers many different angles. The book gives a clear picture of the bumpy but relatively successful implementation of this new governing system in Indonesia. It reveals the existence of many problems and much confusion among stakeholders, and illustrates the ways stakeholders still look to the old system for the answers. The contributions will provide valuable insights to those who praise or criticise the process from the outside, and can offer guidance to other countries that may contemplate doing something similar